The Status of Intimate Partner Violence-related Education for Nurses in Sri Lanka: A Cross-sectional Survey of the Nursing Curricula - Seneviratne, S.; Guruge, S.; Sivayogan, S. (OUSL Journal, 2020)
Intimate Partner Violence (IPV) results in serious short and long-term health consequences, and is a global health problem. Nurses can play a key role in identifying and addressing the health concerns of women subjected to IPV. Yet, nursing curricula often do not adequately-cover this topic. The objective of this study was to examine and describe the current status of the IPV-related education for nurses in Sri Lanka. This study used a descriptive cross-sectional design. A purposive sample of nurse educators from the 24 educational institutions that conduct pre- and post-registration nursing programs in Sri Lanka reviewed their curricula using a pre-tested self-administered questionnaire with closed questions and one open question. Data were analyzed using descriptive statistics and manifest content analysis.
Keywords: education, intimate partner violence, nursing curricula, Sri Lanka